The Effect of Qualitative Exercises to Developing the Ability of Speed Motor Response and the compound skill (V Cat and Rotation - Receiving the Ball – Lay-up shot) for Junior Basketball (Indian Journal of Forensic Medicine & Toxicology, 2021)
The importance of the research lies in the preparation of qualitative exercises in a scientific way, asresearchers see that they affect the development of the ability to speed the movement response and thecomplex skill (V cat rotation, receiving the ball, lay-up shot) for the beginners of basketball. The objectiveof the research was to: Prepare qualitative exercises using auxiliary means, to identify the effect of specificexercises in developing the ability to speed the movement response and the compound skill (V cat rotation,receiving the ball, lay-up shot) for junior basketball. The researchers used the experimental approach insolving the research problem, and on the research community, the research community was identified withthe (12) players of the Al Hilla Sports Club for the 2020-2021 sports season, and they were distributedinto two groups equally in a random way (the draw method), and then dealt with Data using appropriatestatistical methods.
Keywords: Qualitative exercise, speed motor response, complex skill of basketball.